2016
DOI: 10.1007/s00784-016-2005-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bioactive particles on the chemical-mechanical properties of experimental enamel resin infiltrants

Abstract: Resin infiltrants doped with bioactive particles may improve the long-term performance of the treatment of white-spot lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
1
18

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 74 publications
3
44
1
18
Order By: Relevance
“…Considering the phenomenon of polymerization inhibition reported in this study, as well as in previous studies 1012 , it should be noted that there are also reports of various types of BG being successfully incorporated into methacrylate resins with no negative effect on the DC 3,36,44 . These studies have investigated various experimental materials, including Bis-GMA/TEGDMA resin filled with bismuth-oxide-modified BG 3 , Bis-EMA/TEGDMA resin filled with zinc-polycarboxylated BG and BG 45S5 36 , and commercial adhesive systems doped with niobium phosphate-modified BG 44 . The fact that the effect of BG on polymerization apparently varies with the compositions of BG, inert fillers, and resin systems indicates the need for further investigations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Considering the phenomenon of polymerization inhibition reported in this study, as well as in previous studies 1012 , it should be noted that there are also reports of various types of BG being successfully incorporated into methacrylate resins with no negative effect on the DC 3,36,44 . These studies have investigated various experimental materials, including Bis-GMA/TEGDMA resin filled with bismuth-oxide-modified BG 3 , Bis-EMA/TEGDMA resin filled with zinc-polycarboxylated BG and BG 45S5 36 , and commercial adhesive systems doped with niobium phosphate-modified BG 44 . The fact that the effect of BG on polymerization apparently varies with the compositions of BG, inert fillers, and resin systems indicates the need for further investigations.…”
Section: Discussionsupporting
confidence: 79%
“…The potential of unsilanized fillers for the inhibition of polymerization mediated by free radicals has been known for at least four decades 23,25 . Several studies published by different research groups have implied that unsilanized BG fillers can impair the DC of methacrylate resins 10,36,37 . Also, a series of studies performed on the experimental BG-containing composites similar to those based on the Bis-GMA resin system in the present study has indicated that unsilanized BG fillers can diminish the DC in a dose-dependent manner 1012 .…”
Section: Discussionmentioning
confidence: 99%
“…The value found for the Icon DC was close to the values found in other studies, that is, from 50-56% DC. 25,26 By comparing the results obtained using the commercial materials with the supposedly experimental analog (100% TEGDMA)-showing just 32.7% of DC under the same test conditions-it is clear that the remaining experimental groups can be compared only with the experimental control. As expected, raising the temperature led to improved DC, owing to increased molecular mobility and decreased viscosity of the system.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to traditional enamel repair methods, our enamel repair with amorphous ceramics is outstanding (Figure i). Both the Young's modulus and hardness of E‐Amorphous ZrO 2 surpassed the values of enamel repaired by remineralization and with a composite resin, which showed a similar behavior to the E‐Sound samples (Figure i). To the best of our knowledge, the adoption of amorphous ZrO 2 in the fields of enamel repair has not been previously reported, and our enamel repair approach has been proven advantages, indicating great potential for future clinical applications.…”
mentioning
confidence: 66%